The Influence Of Work Culture, Employee Commitment And Performance Appraisal On Job Satisfaction PT. Air Minum Giri Menang (Perseroda) Mataram City - NTB - Pramono Bagus Pratama; Dudung Hadiwijaya; Ismail Marzuki; M Muljadi (Eduvest - Journal of Universal Studies, 2024)
Comprehensive, integrated and sustainable management of water resources plays an important role in creating national water security, including meeting the basic needs of clean water for the community. PT Air Minum Giri Menang (Perseroda) in Mataram, NTB, as one of the water resources managers, faces challenges in improving employee job satisfaction, which has an impact on the quality of public services. This study aims to analyze the influence of work culture, employee commitment, and performance appraisal on employee job satisfaction of PT Air Minum Giri Menang (Perseroda) in Mataram City, NTB. This research uses quantitative methods with explanatory research type. The research population included all permanent employees of PT Air Minum Giri Menang (Perseroda) totaling 179 people, with a sample of 45 permanent employees selected based on a certain percentage. The data analysis techniques used include classical assumption tests, multiple linear regression tests, and hypothesis testing. The results showed that the variables of work culture, employee commitment, and performance appraisal were normally distributed and suitable for analysis using multiple linear regression. This study found that the three variables have a significant influence on employee job satisfaction.